2017
DOI: 10.1371/journal.pone.0189223
|View full text |Cite
|
Sign up to set email alerts
|

Systematic integrative analysis of gene expression identifies HNF4A as the central gene in pathogenesis of non-alcoholic steatohepatitis

Abstract: Non-alcoholic fatty liver disease (NAFLD) is the most common chronic liver disease in the Western world, and encompasses a spectrum from simple steatosis to steatohepatitis (NASH). There is currently no approved pharmacologic therapy against NASH, partly due to an incomplete understanding of its molecular basis. The goal of this study was to determine the key differentially expressed genes (DEGs), as well as those genes and pathways central to its pathogenesis. We performed an integrative computational analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 53 publications
1
53
0
Order By: Relevance
“…Multiple studies have shown the importance of various key regulators and genetic alterations for the development and the progression of NAFLD [67,68]. However, there are only a few attempts to analyze NAFLD from a systems biology perspective, i.e., decoding how these different regulators interact in the context of NAFLD [17,[69][70][71][72]. Thus, mechanism-based modeling studies are required to elucidate these mechanisms from a dynamical systems perspective.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have shown the importance of various key regulators and genetic alterations for the development and the progression of NAFLD [67,68]. However, there are only a few attempts to analyze NAFLD from a systems biology perspective, i.e., decoding how these different regulators interact in the context of NAFLD [17,[69][70][71][72]. Thus, mechanism-based modeling studies are required to elucidate these mechanisms from a dynamical systems perspective.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are only a few attempts to analyze NAFLD from a systems biology perspective, i.e. decoding how these different regulators interact in the context of NAFLD [17,[62][63][64][65]. Thus, mechanismbased modeling studies are required to elucidate these mechanisms form a dynamical systems perspective.…”
Section: Discussionmentioning
confidence: 99%
“…Hepatocyte Nuclear Factor 1Ī± (HNF1Ī±) [16][17][18]. HNF4Ī± is an established master regulator of induction and maintenance of the hepatic cell state [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…First, the DE genes were processed using Ingenuity Pathway Analysis (IPA). Forty-six enriched pathways were found, 22 of which (or 47.8%) were related to NAFLD (Supplementary Table 5), like for example "adipogenesis", "sirtuin signalling", "mTOR signalling", "PI3K/Akt signalling", "B Cell receptor signalling", and "hepatic fibrosis" 13,14,26,27 .…”
Section: Blood Transcriptomes Of Dd and Lw Pigs Revealed A Potential mentioning
confidence: 99%